2022
DOI: 10.1037/aca0000309
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of psychological vulnerabilities and resources in artists and nonartists.

Abstract: The present study was inspired by Barron's (1963) description of creative individuals as "occasionally crazier, yet adamantly saner" than the general population. As suggested by this description, we hypothesized that some individuals embody a pattern of both psychological vulnerabilities and resources and that this pattern is more likely to be present in artists than nonartists. We analyzed intraindividual patterns of psychological vulnerabilities (anxiety, depression, stress) and resources (psychological well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 96 publications
1
3
0
Order By: Relevance
“…In addition, student actors were more capable than other undergraduates at identifying facial expressions related to pride, but less capable than other undergraduates at identifying facial expression related to anger. This finding is related to another recent piece from Ivcevic and colleagues [ 20 ] who found that, despite the strong negative correlation at the population level between psychological vulnerabilities such as anxiety and depression and psychological resources such as self-acceptance and hope, creative experts (i.e., fine arts faculty) exhibited simultaneously high levels of both psychological vulnerabilities and resources, implying that creative experts may be fruitfully utilizing both their negative and positive psychological attributes to support their artistic expression. These findings are supported by a relatively long line of psychological research from scholars such as Thalia Goldstein and Ellen Winner [ 21 24 ] who have shown that arts education, and specifically training in acting techniques, can support children’s development of emotional regulation, theory of mind, and other positive psychological attributes, including the capacity to safely express negative emotions.…”
Section: Introductionsupporting
confidence: 80%
“…In addition, student actors were more capable than other undergraduates at identifying facial expressions related to pride, but less capable than other undergraduates at identifying facial expression related to anger. This finding is related to another recent piece from Ivcevic and colleagues [ 20 ] who found that, despite the strong negative correlation at the population level between psychological vulnerabilities such as anxiety and depression and psychological resources such as self-acceptance and hope, creative experts (i.e., fine arts faculty) exhibited simultaneously high levels of both psychological vulnerabilities and resources, implying that creative experts may be fruitfully utilizing both their negative and positive psychological attributes to support their artistic expression. These findings are supported by a relatively long line of psychological research from scholars such as Thalia Goldstein and Ellen Winner [ 21 24 ] who have shown that arts education, and specifically training in acting techniques, can support children’s development of emotional regulation, theory of mind, and other positive psychological attributes, including the capacity to safely express negative emotions.…”
Section: Introductionsupporting
confidence: 80%
“…2019; Cassidy 2016; Dickinson & Dickinson 2015; Downes 2017; Ivcevic et al . 2020; Luthar et al . 2000; Reed et al .…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Vulnerability, agency, self-actualisation, self-efficacy and resilience appear as closely related concepts across a range of resilience research (Ahmed Shafi & Templeton 2020; Brewer et al 2019;Cassidy 2016;Dickinson & Dickinson 2015;Downes 2017;Ivcevic et al 2020;Luthar et al 2000;Reed et al 2019;Wilson et al 2019). Resilience and creativity are often linked through the concept of flexible thinking and the ability to withstand ambiguity.…”
Section: Theme 3: Meaningfulnessmentioning
confidence: 99%
“…A certain amount of skepticism surrounding the “mad artist” moniker is warranted (Schlesinger, 2009). Though many creative individuals experience mental health issues, it should be acknowledged that the personalities of creators are characterized by “multiplicative” factors and consist of an unusual synthesis of strengths and vulnerabilities which manifest in both healthy and pathological behaviors (Ivcevic, Grossman, & Ranjan, 2020; Kaufman & Gregoire, 2015). While some eminent creators have had mental health difficulties, many have led mainly healthy balanced lives (Hughes, 2019).…”
Section: Artistic Creativity and Psychopathologymentioning
confidence: 99%